Pengembangan Ilustrasi Pada Buku Pelajaran Lingkungan dan Budaya Jakarta Tingkat Sekolah Dasar - Ratih Mahardika (Universitas Persada Indonesia YAI, 2022)
Jakarta's environmental and cultural education (PLBJ) is one of the subjects needed to maintain theconcept of value of life community and Betawi cultural environment for future generations, especiallyelementary students. Submission of PLBJ material in schools is conveyed through textbooks in which areintroduced Betawi traditional games, Betawi folklore, Betawi arts, and matters relating to the environment.The material presented is not only in the form of description but also in the form of illustrations. However,the composition between the descriptions and illustrations is not balanced and affects students' interest inreading at school. Illustrations in books can be said to be mandatory especially for elementary books. Becauseinteresting illustrations will stimulate children's curiosity and motivation to read books. Because of this, it isnecessary to develop illustrations in accordance with the book material using methods educational researchand development which have 4 stages of process (4D), namely define (needs analysis of illustrations), design(illustration design), develop (combining the results of illustrations with material in the form of descriptions),and disseminate (see responses from students and teachers concerned). The purpose of this research is todevelop illustrations about the environment and culture of Jakarta, especially the traditional game DampuBulan which can later be used as part of the development of elementary school PLBJ subject matter.abstrack dalam bahasa Inggris.